Peningkatan Pengetahuan Pencegahan HIV/AIDS melalui Pelatihan Kader PMR di SMP Negeri 2 Boyolali - Kusumaningtyas, Bethari Mukti; Umaroh, Ayu Khoirotul (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Based on the Indonesian Ministry of Health's Executive Report for the First Quarter (January-March) of 2022, there were 4,841 reported cases of HIV/AIDS infections. It is indicated that 5-10% of unmarried men aged 15-24 years have engaged in risky sexual activities, reinforcing concerns about the increasing risk of sexual behavior among adolescents. The youth members of the Red Cross (PMR) play a critical role in schools as peer educators, peer leaders, and peer supporters. Therefore, a training program was conducted to enhance the knowledge of PMR members about HIV/AIDS. Method: The training was implemented at SMPN 2 Boyolali, involving 104 participants in three stages: situational analysis, implementation, and evaluation. The training material was adapted from the training manual